Analysis of the operations of an intermodal barge terminal. (1st January 2014) - Verdonck, Lotte; Caris, An; Ramaekers, Katrien; Janssens, Gerrit K.
This paper studies the operations of intermodal barge terminals. The objective is to increase the terminal's efficiency by supporting the operational planning of the terminal operator. For this purpose, a review on general and process-specific barge terminal planning problems, discussed in current scientific literature, is provided. This theoretical knowledge is validated in practice by means of a comparison with operational planning realities at Haven Genk, a Belgian trimodal terminal. Finally, simulation studies based on Haven Genk data are performed to investigate whether vessel size and number of vessels in use have an impact on barge terminal efficiency.